On the numerical index of absolute symmetric norms on the plane. Issue 5 (4th April 2021) - Merí, Javier; Quero, Alicia
ABSTRACT: We give a lower bound for the numerical index of two-dimensional real spaces with absolute and symmetric norm. This allows us to compute the numerical index of the two-dimensional real L p -space for 3 / 2 ≤ p ≤ 3 .